Advanced Microsoft Access 2010 - Miles, Timothy; Safari eBooks ([S.l.] : CompuWorks, 2013)
"This course builds on the Introduction and Intermediate courses to show techniques to bring all of the different Access objects together to make a cohesive application. It does this by showing the viewer how and why Microsoft Access utilizes the Properties and Events of the different objects. Finally, the course shows the viewer how to create macros using the new Macro editor and how to select the proper Control and Event for the best possible outcome. "--Resource description page.
Title from title screen.
Publication information taken from resource description page (Safari, viewed May 16, 2013).
Presenter, Timothy Miles.
Keywords: Microsoft Access; Database management; Electronic books